Understanding the impacts of surface compositions on the in-vitro dissolution and aerosolization of co-spray-dried composite powder formulations for inhalation - Mangal, Sharad (Pharm Res, 2018)
PURPOSE: Dissolution behavior of dry powder inhaler (DPI) antibiotic formulations in the airways may affect their efficacy especially for poorly-soluble antibiotics such as azithromycin. The main objective of this study was to understand the effects of surface composition on the dissolution of spray dried azithromycin powders by itself and in combination with colistin. METHODS: Composite formulations of azithromycin (a poorly water-soluble molecule) and colistin (a water-soluble molecule) were produced by spray drying. The resultant formulations were characterized for particle size, morphology, surface composition, solid-state properties, solubility and dissolution. RESULTS: The results demonstrate that surfaces composition has critical impacts on the dissolution of composite formulations. Colistin was shown to increase the solubility of azithromycin. For composite formulations with no surface colistin, azithromycin released at a similar dissolution rate as the spray-dried azithromycin alone. An increase in surface colistin concentration was shown to accelerate the dissolution of azithromycin. The dissolution of colistin from the composite formulations was significantly slower than the spray-dried pure colistin. In addition, FTIR spectrum showed intermolecular interactions between azithromycin and colistin in the composite formulations, which could contribute to the enhanced solubility and dissolution of azithromycin. CONCLUSIONS: Our study provides fundamental understanding of the effects of surface concentration of colistin on azithromycin dissolution of co-spray-dried composite powder formulations.